“Smart cities methodology (Scml) : uma metodologia em smart cities baseada em valor público” - Porto, Josiane Brietzke (2018)
Smart city is an approach to managing and coping with urban challenges in search for innovative solutions leading to better quality of life and sustainability in cities. Several initiatives have been undertaken, with a significant worldwide growth trend in the coming years. Such initiatives, however, may require non-trivial public investment, and failures resulting from them can have important consequences such as monetary loss, loss of reputation, reduced confidence and lack of public value. This research aims at setting a methodology in smart cities composed of a reference model and an assessment method from the Public Value perspective. These artifacts were evaluated based on the perception of 23 representatives of the Quadruple Helix (government, industry, university and citizens) and on the results of the applicability in practice, through an initial pilot evaluation, in the city of Nova Santa Rita. It follows Design Science as its epistemological paradigm and Design Science Research as its method, uniting theoretical and methodological rigor as well as practical utility for society. The results showed that the artifacts developed in this research can help in the design and assessment of smart cities in a gradual way, bringing together best practices considered intelligent and that allow for the expansion and/or generation of Public Value, consisting of a prescriptive scientific contribution. Among the contributions are the protocol, contingency and construction heuristics, which detail how these artifacts were rigorously designed and developed, under the Design Science paradigm, to solve the problem identified in this research. They are specific and useful knowledge, generated from this research, aimed at the practice and resolution of real problem, and can be used for future evolutions of the artifacts developed in the research and/or design of new artifacts, in different contexts and classes of problems.